Flexibility as risk factor for stress-fracture development in South African male soldiers - Paola S. Wood; P. E. Krüger (South African Family Practice, 2015)
Background: Stress fractures are a common military training injury. Flexibility of muscles and joints may directly influence stress-fracture risk by way of altering the forces applied to bone. Hip external rotation and ankle plantar- and dorsiflexion have been inconsistently reported to pose a risk to stress fracture development in military soldiers. Thus this study aimed to present results that could help define the risk flexibility may pose in the development of stress fractures amongst military male soldiers.